Apostolic Works according to the Spirit of Opus Dei - Dorota Grądalska (Nicolaus Copernicus University in Toruń, 2014)
This article discusses the issue of the apostolate of members and cooperators of the Prelature of Opus Dei. It situates the apostolate in the Opus Dei doctrine and indicates its significance. This text focuses on the presentation of selected institutional apostolic works within Poland. It refers to extracts of the writings of Josemaría Escrivá, who justifies the need for the existence of these initiatives and stresses their educational and formative character. The activities of the mentioned organizations are presented in the context of social role of religion and the project of social structures transformation.